Evaluasi Kapasitas Drainase Kota Bangkinang Bagian Tengah (Kelurahan Langgini) - Putra, Jasman Adi; Sujatmoko, Bambang; Fauzi, Manyuk (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The flooding area in Bangkinang city were around DI Panjaitan road and suburban of Petai I river, where drainage capacity can’t received most flow discharge that is flowed from catchment area, then the channel that have not enough capacity cause the discharge flows into was DI Panjaitan road channel and petai I river not optimal, flooding and inundated happened. This condition causes people who live in that area uncomfortable. This study aims to analyze the drainage system and the channel capacity to drain runoff so that flood was not happened in flood area. Rainfall station data of Pasar Kampar for 15 years used to determine planed rainfall by using 10 years return period and get planned rainfall (R24) of 135,990 mm. From the data of topographic, flow patterns and planed rainfall used to calculate discharge for the required dimension channel. Results of research show that the existing capacity of channel dimension can’t enough to receive the discharge, so that it is done the normalization on channel e.g : SD Panjaitan Kn4, SD Petai1 10, SD Petai1 12 and SD Petai1 13.Key words: Bangkinang, floods, rainfall, discharge, drainage channel.